A inserção da educação em direitos humanos no ensino superior no Brasil: o caso do IFPB - Campus Campina Grande - Hermida, Claudiene Fátima de Souza (2018)
Human rights education in higher education has been considered in the set of national and international standards as being of fundamental importance in the formation of ethical citizens committed to respect for human rights. This work aims to analyze how human rights education is inserted in Higher Education at the Federal Institute of Education, Science and Technology of Paraíba (IFPB) Campina Grande campus. As specific objectives was intended: to conceptualize and to base education in and for human rights, tracing the historical-social process that allowed the insertion of human rights in higher education institutions and their international and national normative frameworks; to contextualize the policy of human rights education in Higher Education in Brazil; to raise the initiatives in the normative and pedagogical field regarding human rights in the IFPB, in order to contextualize and analyze the actions developed in the Campina Grande Campus in the scope of teaching, research, and extension. As temporal delimitation, we start with Resolution No. 146/2015 - IFPB, which approves and regulates the National Human Rights Education Guidelines within the IFPB, until 2017, year in which we began the research. Having identified all the initiatives regarding human rights education at the general IFPB level, we started with the Campina Grande campus case study, identifying the insertion of education in and for human rights in the higher courses offered by this unit education. From a methodological point of view, this is a qualitative research with emphasis on documentary and exploratory research. As a technique of analysis of the data collected in the documentary research was used content analysis that subsidized the analysis and interpretation of the data. The research indicates that there are important achievements from the point of view of IFPB internal regulations. However, we cannot affirm that these regulations have been constituted, at least in the Campina Grande campus, in the effective insertion of human rights education within the framework of the teaching, research and extension. There is the offer of disciplines in the subject of Human Right and research and extension projects that, although of profound relevance in the theme, do not approach the subject in the perspective of human rights. The study corroborates the understanding that in order to work in the human rights perspective, normative achievements are important and offer a direction to work, but it is necessary to raise the awareness of the subjects involved in the process, since human rights education is done in action.